Religious Beliefs Mesopotamia and their infiuence on Greek antagonists - Tawaklna, Abraheem; Deaf, Kenana (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Religious beliefs and their symbols and legends are the most important intellectual product of man in his life. It is an urgent need and is the basis of his life and man in all parts of this earth was thinking and trying to explain the universe and hence arose religious beliefs and legends.The research studies the most important points of similarity between the most important epics and legends of Mesopotamia and between Greek epics and legands in addition to religious beliefs and Goddess and its symbols. With clarification and confirmation that the epics, legends and the Greek goddess are only part of the civilization of Mesopotamia and moved to it through the ages. He mentioned the details of the espics and their heroes with a statement of different names only and an explanation of the most important Rafidian goddesses and their different names in the Gree; civilization.